Fighting fire with science - Dimitropoulos, Stav (Nature (London), 2019)
Wildfires are becoming more and more frequent around the world, making expertise in the field a hot commodity. Wildfires are becoming more and more frequent around the world, making expertise in the field a hot commodity. Mike Flannigan